Electrochemical determination of maleic anhydride using gold nanoparticles and cysteine - Noh, Teh Ubaidah; Aziz, Azila Abd; Rosli, Nur Ayshah; Khalid, Nurul Izzah (Malaysian Institute of Chemistry, 2024)
This study introduces an innovative approach for the rapid detection of maleic anhydride haptenation in skin sensitization studies. The method involved the modification of a screen–printed carbon electrode (SPCE) with cysteine and gold nanoparticles (AuNPs) using electrodeposition and self–assembled monolayer (SAM) techniques. These modifications created an efficient platform for detecting maleic anhydride interactions. To characterize the modified SPCE, various analytical techniques were employed. The electrochemical properties of the modified SPCE were thoroughly investigated using electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). These techniques provided valuable insights into the detection capabilities of the modified SPCE. Notably, the (electrodeposition of AuNPs, self–assembled of AuNPs and cysteine on SPCE) ETSC modified SPCE exhibited optimal maleic anhydride detection through impedance measurements. The modified electrode demonstrated good stability at room temperature and good reproducibility, underscoring its potential as a rapid detection sensor for initial skin sensitizer screening in skincare products.